Propagation of Enzyme‐Induced Surface Events inside Polymer Nanoassemblies for a Fast and Tunable Response. (6th May 2018) - Zhuang, Jiaming; Seçinti, Hatice; Zhao, Bo; Thayumanavan, S.
Abstract: We report a new molecular design strategy that allows for the propagation of surface enzymatic events inside a supramolecular assembly for accelerated molecular release. The approach addresses a key shortcoming encountered with many of the currently available enzyme‐induced disassembly strategies, which rely on the unimer–aggregate equilibria of amphiphilic assemblies. The enzymatic response of the host to predictably tune the kinetics of guest‐molecule release can be programmed by controlling substrate accessibility through electrostatic complexation with a complementary polymer. Accelerated guest release in response to the enzyme is shown to be accomplished by a cooperative mechanism of enzyme‐triggered supramolecular host disassembly and host reorganization.